2018
DOI: 10.3892/ijmm.2018.4030
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulation of transcription in the reversal of morphine tolerance: Microarray analysis of differential gene expression

Abstract: Tolerance and associated hyperalgesia induced by long-term morphine administration substantially restrict the clinical use of morphine in pain treatment. Melatonin, a neurohormone released by the pineal gland, has been demonstrated to attenuate anti-nociceptive morphine tolerance. The present study investigates differentially expressed genes in the process of morphine tolerance and altered gene expression subsequent to melatonin treatment in chronic morphine-infused ratspinal cords. Morphine tolerance was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Our microarray analysis also showed that a single i.t. injection of melatonin in the morphine-tolerant rat inverts the bulk of genes down/upregulated by the chronic morphine treatment [ 39 ], suggesting a crucial genetic regulation of high-dose melatonin treatment and consequently the morphine tolerance reversal. However, the effect of long-term administration of melatonin directly targeting the spinal cord on a morphine-tolerant rat model has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our microarray analysis also showed that a single i.t. injection of melatonin in the morphine-tolerant rat inverts the bulk of genes down/upregulated by the chronic morphine treatment [ 39 ], suggesting a crucial genetic regulation of high-dose melatonin treatment and consequently the morphine tolerance reversal. However, the effect of long-term administration of melatonin directly targeting the spinal cord on a morphine-tolerant rat model has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that melatonin has excellent anti‐inflammatory and antioxidant effects [133,134]. Melatonin regulates the expression of genes related in morphine tolerance [129,135‐137]; this effect may be a result of its potent anti‐inflammatory and antioxidant properties ( Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…This revealed the characteristics of the transcriptome in the T1-T4 spinal cord following cardiac I/R injury and the specific spinal segment that innervates the heart serves a significant role in cardiac I/R injury. Cheng et al (53) reported that melatonin regulation of the transcriptome was associated with the reversal of morphine tolerance by transcriptomic analysis of the L5-S3 segmental spinal cord. Mohrman et al (54) revealed the spinal cord transcriptomic and metabolic patterns in a excitotoxic injection injury model of syringomyelia.…”
Section: Discussionmentioning
confidence: 99%